Audit Professional Proficiency and Audit Stability: An Empirical Research Involving Certified Public Accountants (CPAs) in Thailand - Wangcharoendate, Suwan (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2019)
The objective of this research is to empirically examine the effects of audit professional proficiency on audit stability. The sample was 355 Certified Public Accountants (CPAs) in Thailand. A questionnaire was used to collect data and the analysis employed the Ordinary Least Squares (OLS) regression analysis. The results indicate that audit professional proficiency has a positive impact on audit stability through audit outcomes as the mediators. In addition, antecedent variables include continual professional training. audit technological attentions and audit process improvement have a positive relationship with audit professional proficiency. Regarding moderating effects, professional regulation has a positive relationship to audit professional proficiency and audit outcomes. While, audit market competition is shown to be partially positively supported between antecedent variables and audit professional proficiency.